1975
DOI: 10.1007/bf00225107
|View full text |Cite
|
Sign up to set email alerts
|

Intranuclear and cytoplasmic annulate lamellae in grasshopper spermatocytes (Genus Melanoplus)

Abstract: Intranuclear and cytoplasmic annulate lamellae were studied in grasshopper spermatocytes (Melanoplus) with the electron microscope. Although cytoplasmic annulate lamellae were observed in all three species examined, intranuclear annulate lamellae were found in only one species. The intranuclear annulate lamellae encompass certain nuclear material adjacent to the nuclear envelope forming a vesicle that is extruded into the spermatocyte cytoplasm. In this same species, cytoplasmic annulate lamellae are seen cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1976
1976
1984
1984

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…On the other hand, it is tempting to speculate that the ER-related sructures take part in inhibin synthesis. Although the cellular origin of this protein [Franchimont et al, 1977] is not yet well known, it has been suggested that the spermatids might play a role in this synthesis [Setchell et al, 1977], AL have been described in a great variety of cell types, mainly in germinal, embryonic, neoplastic and mitotic cells [ Wischnitzer, 1970], In seminiferous tubules they have been observed in human Sertoli cells [Bawa, 1963], invertebrate germ cells [Ruthmann, 1958;Hoage and Kessel, 1968;Pool and Hoage, 1975], fish spermatogonia [Schjeide et al, 1972], rat spermatids [Swift, 1956] and in human spermatocytes and spermatids [Smith and Berlin, 1977], Cytochemical analysis of AL revealed that the electrondense material between AL membranes cor responds to protein, while nucleic acids were not detected [Dhainaut, 1973;Smith and Berlin, 1977], Although different hypotheses upon the origin of the AL have been suggested [De Brahander and Borgers, 1975], Smith and Berlin [1977] assume that the origin of AL in human spermatogenesis is the nuclear envelope. This hypothesis is based on the connections observed between both types of membrane and has been pointed out previ ously for the AL of other cells [Kessel, 1964[Kessel, , 1968, In human spermatids, Horstmann [1961] described 'cytoplasmic lamellar bodies', considering them as a pathway for nuclear material to enter the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is tempting to speculate that the ER-related sructures take part in inhibin synthesis. Although the cellular origin of this protein [Franchimont et al, 1977] is not yet well known, it has been suggested that the spermatids might play a role in this synthesis [Setchell et al, 1977], AL have been described in a great variety of cell types, mainly in germinal, embryonic, neoplastic and mitotic cells [ Wischnitzer, 1970], In seminiferous tubules they have been observed in human Sertoli cells [Bawa, 1963], invertebrate germ cells [Ruthmann, 1958;Hoage and Kessel, 1968;Pool and Hoage, 1975], fish spermatogonia [Schjeide et al, 1972], rat spermatids [Swift, 1956] and in human spermatocytes and spermatids [Smith and Berlin, 1977], Cytochemical analysis of AL revealed that the electrondense material between AL membranes cor responds to protein, while nucleic acids were not detected [Dhainaut, 1973;Smith and Berlin, 1977], Although different hypotheses upon the origin of the AL have been suggested [De Brahander and Borgers, 1975], Smith and Berlin [1977] assume that the origin of AL in human spermatogenesis is the nuclear envelope. This hypothesis is based on the connections observed between both types of membrane and has been pointed out previ ously for the AL of other cells [Kessel, 1964[Kessel, , 1968, In human spermatids, Horstmann [1961] described 'cytoplasmic lamellar bodies', considering them as a pathway for nuclear material to enter the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…In the seminiferous tubules they have been observed in invertebrate germ cells [6,14,151, fish spermatogonia 1171, rat spermatids [20,221, human spermatocytes and spermatids [I 1, 191, and human Sertoli cells [l] . The present report provides ultrastructural evidence on AL formation from the rough endoplasmic reticulum (RER) in pubertal human Sertoli cells.…”
Section: Introductionmentioning
confidence: 99%